Blue ocean strategy : - Kim, W. Chan (Harvard Business Review Press, 2015)
This global bestseller, embraced by organizations and industries worldwide, challenges everything you thought you knew about the requirements for strategic success. Now updated with fresh content from the authors, Blue Ocean Strategy argues that cutthroat competition results in nothing but a bloody red ocean of rivals fighting over a shrinking profit pool